MEMBERSHIP APPLICATION PROGRAMS ON PARTAI KEADILAN PERSATUAN INDONESIA PARTY USING MICROSOFT ACCESS 2000 - Uus Ali Husni; Don Elsyafitra, SKom (Jurnal Sistem Informasi, 2004)
Issue of membership of political parties is very crucial to living-dead, or forward - pullback organization, requiring special handling and seriously. party membership system manual has been used of course very ineffective and inefficient for the performance of the organization, for the necessary changes to the membership of the manual system to a computerized system that can operate effectively and efficiently. Therefore, the authors try to make this scientific research to facilitate the process of membership in the Indonesian Justice and Unity Party (PKP Indonesia) using Microsoft Access 2000.